Nano calcium carbonate for single-component dealcoholized silicone adhesive and preparation method thereof

Through the improved preparation method, the performance of nano calcium carbonate is improved by using modifiers and coupling agents, and the problems of unstable production and insufficient performance of single-component dealcoholized silicone glue are solved, and higher storage stability is achieved , adhesion and vulcanization rate.

CN117801569BActive Publication Date: 2025-02-25SHANXI XINTAI HENGXIN NANO MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311836373.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-02-25
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

The single-component dealcoholized silicone glue is unstable during the production process, has high requirements for nanocalcium, and has problems such as poor storage stability, slow vulcanization speed and poor adhesion.

Method used

Using a preparation method, by carbonizing the Ca(OH)2 semen slurry, adding modifier I to modify it, a nano calcium carbonate slurry was obtained, and nano calcium carbonate powder was obtained after pressure filtering and drying, and continuously in the drying process. To the modification, titanate coupling agent and silane coupling agent are added to improve their performance.

Benefits of technology

The storage stability, adhesion and vulcanization speed of the dehydration glue are significantly improved, the modulus is reduced, the elongation and extrusion amount are improved, and the high quality and stability of the adhesive are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004637704320000131
    Figure BDA0004637704320000131
  • Figure BDA0004637704320000141
    Figure BDA0004637704320000141
  • Figure BDA0004637704320000151
    Figure BDA0004637704320000151
Patent Text Reader

Abstract

The present invention relates to the technical field of nano calcium carbonate, and in particular to a single-component dealcoholized nano calcium carbonate for silicone adhesive and a preparation method thereof. The preparation method comprises the following steps: S1, carbonizing Ca(OH)2 refined slurry to obtain a carbonized liquid; S2, heating the carbonized liquid to 55-75°C, adding a modifier I for modification, obtaining a nano calcium carbonate slurry, and obtaining a nano calcium carbonate powder after filter pressing and drying; S3, modifying the nano calcium carbonate powder with a modifier II to obtain a dealcoholized nano calcium carbonate for silicone adhesive; the modifier I is composed of C 16 ‑C 20 One of fatty acid and its salt, sulfonate and its ester, and advanced phosphate is mixed with chelated titanate coupling agent in a mass ratio of 2-4:1; modifier II is mixed with titanate coupling agent and silane coupling agent. The one-component dealcoholized silicone adhesive prepared from nano calcium carbonate has excellent properties of low modulus, high elongation, high adhesion and high storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano calcium carbonate, and in particular to nano calcium carbonate for single-component dealcoholized silicone adhesive and a preparation method thereof. Background Art

[0002] Silicone adhesive is widely used in various construction, interior decoration and industrial electronics fields due to its excellent cold resistance, heat resistance, aging resistance, waterproof and moisture resistance. The main types are deketoxime type, deacetic acid type, dealcoholization type, etc. Single-component dealcoholization silicone adhesive has been increasingly used in the market in recent years because the small alcohol molecules released after vulcanization are non-corrosive, environmentally friendly, and have low odor. They are non-corrosive to the substrates they contact, have good adhesion, and have good physical and mechanical properties and electrical properties. However, the production process of single-component dealcoholization adhesive is unstable, and it has high requirements for nano-calcium. In addition, single-component dealcoholization adhesive has always had the disadvantages of poor storage stability, slow vulcanization speed, and poor adhesion. The problems of slow vulcanization speed and poor adhesion have been greatly improved by the technical personnel of each dealcoholization adhesive manufacturer through certain formula improvements, but the problem has not been completely improved.

[0003] Nano calcium carbonate accounts for about 50% of silicone adhesive, and the quality of nano calcium carbonate has a huge impact on the quality of silicone adhesive. Through experiments, it is verified that on the basis of improving the silicone adhesive formula, improving the quality of nano calcium carbonate can greatly improve or enhance the storage stability, adhesion and vulcanization speed of dealcoholized adhesive. Existing nano calcium carbonate products on the market have been widely used in silicone adhesive systems, and also have a certain amount in single-component dealcoholized adhesive systems, but there is a problem that modulus, elongation and adhesion cannot be taken into account at the same time. Summary of the invention

[0004] In order to take into account the modulus, elongation and adhesion of the single-component dealcoholized silicone adhesive, the present invention provides a nano calcium carbonate for a single-component dealcoholized silicone adhesive and a preparation method thereof.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A method for preparing nano calcium carbonate for dealcoholized silicone adhesive comprises the following steps:

[0007] S1, carbonizing the Ca(OH)2 refined slurry to obtain a carbonized liquid;

[0008] S2, heating the carbonized liquid to 55-75° C., adding the saponified modifier I for modification to obtain nano calcium carbonate slurry, and obtaining nano calcium carbonate powder after filter pressing and drying;

[0009] S3, heating the carbonized liquid to 55-75°C, adding a modifier I having a calcium carbonate content of 2.5%-3.5%, and stirring at this temperature for 1h-3h to obtain a nano-calcium carbonate slurry, and obtaining a nano-calcium carbonate powder after filter pressing and drying;

[0010] S4, adding 0.5%-1.5% by weight of modifier II to the nano-calcium carbonate powder based on dry calcium carbonate, stirring for 0.5-1h to obtain the single-component dealcoholized nano-calcium carbonate for silicone adhesive;

[0011] The modifier I is composed of C 16 -C 20 A fatty acid and its salt, a sulfonate and its ester, and a higher phosphate ester are mixed with a chelated titanate coupling agent in a mass ratio of 2-4:1;

[0012] The modifier II is prepared by mixing a titanate coupling agent and a silane coupling agent in a mass ratio of 1:1.

[0013] As a preferred preparation method of the present invention, the C 16 -C 20 The fatty acid is selected from one or more of palmitic acid, stearic acid, linoleic acid, oleic acid, dienoic acid, linolenic acid, arachidonic acid and eicosapentaenoic acid; the sulfonate is selected from one or more of linear alkylbenzene sodium sulfonate and α-olefin sodium sulfonate; the higher phosphate is selected from one or more of monoalkyl phosphate, dialkyl phosphate and trialkyl phosphate; the chelated titanate coupling agent is selected from one of a chelate solution of bis(dioctyl pyrophosphate)ethylene titanate and triethanolamine, ethylene chelated pyrophosphate acyloxy titanate and bis(dioctyl pyrophosphate)ethylene titanate.

[0014] As a preferred preparation method of the present invention, the titanate coupling agent is selected from one of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, isopropyl dioleyl acyloxy(dioctyl phosphate acyloxy) titanate, bis(dioctyl pyrophosphate ester) ethylene titanate, plant acid type monoalkoxy titanate, pyrophosphate type monoalkoxy titanate, composite phosphoric acid type monoalkoxy titanate, di(octylphenol polyoxyethylene ether) phosphite and tetraisopropyl di(dioctyl phosphite acyloxy) titanate; the silane coupling agent is selected from one of vinyl triethoxy silane, vinyl trimethoxy silane and vinyl tri(β-methoxyethoxy) silane.

[0015] As a preferred preparation method of the present invention, the CaCO3 content of the limestone is ≥98.5%, MgO≤0.5%, the block diameter is 5-10cm, the coke C is ≥78%, the rock-coke ratio is 10-12:1, the calcination temperature is 800℃-1100℃, the calcination time is 48h-96h, and the calcination obtains overburned CaO with an oxalic acid detection activity of 5'-10'.

[0016] As a further preferred embodiment of the preparation method of the present invention, the CaCO3 content of the limestone is ≥98.5%, MgO ≤0.5%, the block diameter is 5-10 cm, the coke C is ≥78%, the rock-coke ratio is 10-12:1, the calcination temperature is 800°C-1100°C, the calcination time is 48h-96h, and the calcination obtains overburned CaO with an oxalic acid detection activity of 5'-10'.

[0017] As a further preferred embodiment of the preparation method of the present invention, the digestion, screening and aging are specifically as follows: the over-burned CaO is digested with 80-100°C hot water, the ash-to-water ratio is 1:5-8, and the digestion is carried out in a continuous digester until the Ca(OH)2 mass concentration is 9%-15%, and the mixture is sieved with a 100-mesh sieve, aged at 50°C-70°C for 100-150h, sieved with a 325-mesh sieve, and water is added to adjust the Ca(OH)2 refined slurry mass concentration to 5%-7%.

[0018] As a preferred embodiment of the preparation method of the present invention, the carbonization is specifically:

[0019] The Ca(OH)2 refined slurry is pumped into the high gravity reactor, the carbonization temperature is 18-22℃, the feed volume is 5-10m 3 , CO2 content 35%-45%, flow rate 55-250L / min, reaction time 15-25min, endpoint pH control 6.5-6.8, add Ca(OH)2 dispersant of 0.5%-1.0% of the mass of the seminal plasma, continue the cyclic carbonization for 1min, stop carbonization, and leave it for 5-10h.

[0020] As a further preferred embodiment of the preparation method of the present invention, the high-gravity reaction unit is composed of 2-3 high-gravity reactors connected in parallel to the same carbonization liquid circulation tank.

[0021] As a further preferred embodiment of the preparation method of the present invention, the dispersant is selected from one or more of triethylhexyl phosphoric acid, polyacrylamide, sodium dodecyl sulfate and sodium oleate.

[0022] As the same inventive concept, the present invention also provides nano calcium carbonate prepared by the preparation method.

[0023] As the same inventive concept, the present invention also provides a dealcoholized silicone adhesive prepared by using the nano calcium carbonate, which is made of the following components by weight:

[0024] 107 glue, 360 copies;

[0025] Silicone oil, 36 parts;

[0026] Nano calcium carbonate, 360 parts;

[0027] Silane coupling agent KH550, 18 parts;

[0028] Silane coupling agent KH560, 20 parts;

[0029] Methyldimethylsilane, 15 parts;

[0030] Organic titanium catalyst, 8 parts.

[0031] As a preferred embodiment of the dealcoholized silicone adhesive of the present invention, the organic titanium Tyzor catalyst is 726.

[0032] The inventive concept and beneficial effects of the present invention:

[0033] (1) Select limestone with high CaCO3 content and calcine it at a relatively high temperature to obtain lime with large primary particles and smooth surface. The oxalic acid activity of the calcined lime is controlled at 5′-10′.

[0034] (2) High temperature digestion, keep warm at 50℃-70℃ for 100h-150h, which is conducive to the complete digestion of lime particles.

[0035] (3) The high-gravity carbonization reactors are connected in parallel to speed up the reaction, so that the generation rate of nano-calcium carbonate is greater than the growth rate, and the particle size is small. The original particle size can be controlled by the number of parallel reactors.

[0036] (4) The carbonization process uses high concentration CO2 gas to increase the synthesis rate of the reaction between Ca(OH)2 and CO2.

[0037] (5) Before the end of carbonization, an organic dispersant, an anionic dispersant or a mixture of the two is added. The anionic dispersant acts as a charge repulsion. When the organic dispersant is adsorbed on the surface of the particles, the layered structure formed can effectively prevent the contact and focusing between the particles, and play a steric hindrance effect. The two dispersing effects have a synergistic effect, which reduces the cohesion of the nano calcium carbonate particles and reduces agglomeration.

[0038] (6) Heat the carbonized liquid and add modifier I to change the hydrophilicity of calcium carbonate to hydrophobicity, specifically C 16 -C 20 Fatty acids and salts, sulfonates include sodium linear alkylbenzene sulfonate and sodium α-olefin sulfonate, higher phosphates include monoalkyl phosphate, dialkyl phosphate and trialkyl phosphate, and chelated titanate coupling agents. Any of the first three can be mixed with the chelated titanate coupling agent. The first three conventional modifiers improve the dispersibility and lipophilicity of the nano-calcium carbonate product, and the coupling agent improves the adhesion and thixotropy of the nano-calcium carbonate in the glue.

[0039] (7) The secondary modification is a dry continuous modification. Modifier II is a titanate coupling agent and a silane coupling agent. The dripping effect is to further improve the material performance, increase the filling amount, elongation, storage stability in the application of glue making, increase the bonding force with the rubber material, and improve the bonding force of the adhesive.

[0040] (8) The pore size of the obtained nano calcium carbonate product is 25-35nm. Experiments have shown that the nano calcium carbonate product within this range has a certain adhesive adsorption property, and will not increase the viscosity and reduce the storage property after being placed and infiltrated due to the pore size being too large.

[0041] (9) The BET of the obtained nano calcium carbonate product is 15-22m 2 / g, moisture ≤0.3%, pH value 8.5-9.5, extrusion volume 60-90g / min, pore size 25-35nm, laser particle size D 50 <1.0um,D 100 <5.0um. Moderate specific surface area, low water content and pH value can effectively reduce the modulus of the adhesive. High extrusion volume can increase the elongation of the adhesive. The pore size is uniform and the laser particle size is small, indicating that the product particle size is uniform and well dispersed. DETAILED DESCRIPTION

[0042] The present invention is described in detail below in conjunction with specific examples, but it should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.

[0043] Example 1

[0044] A method for preparing nano calcium carbonate for dealcoholized silicone adhesive

[0045] (1) limestone is used as a raw material, and Ca(OH)2 refined slurry is obtained through calcination, digestion, screening and aging, and the Ca(OH)2 refined slurry is carbonized to obtain a carbonized liquid;

[0046] The limestone has a CaCO3 content of ≥98.5%, MgO ≤0.5%, a block diameter of 5-10 cm, a coke C of ≥78%, and a rock-coke ratio of 12:1;

[0047] Calcination: calcining the limestone at 800°C-900°C for 96 hours to obtain overburned CaO with an oxalic acid detection activity of 5';

[0048] Digestion, sieving and aging: add 85°C hot water to the burnt CaO for digestion, with an ash-water ratio of 1:8, and use a continuous rotary digester to digest until the Ca(OH)2 mass concentration reaches 15%, pass through a 100-mesh sieve, keep warm at 50°C for aging for 100 hours, pass through a 325-mesh sieve, and add water to make the Ca(OH)2 refined slurry mass concentration reach 6%;

[0049] Carbonization: Pump the Ca(OH)2 refined slurry into the supergravity reactor, the carbonization temperature is 18℃, the feed volume is 10m 3 , CO2 content 36%, flow rate 210L / min, reaction time 22min, endpoint pH control 6.55, add Ca(OH)2 seminal slurry mass 0.5% dispersant, continue cyclic carbonization for 1min, stop carbonization, detect nano calcium carbonate pore size of 35nm, leave for 8h, and obtain carbonized liquid;

[0050] The high-gravity reaction unit of this embodiment is composed of two high-gravity reactors connected in parallel on the same carbonization liquid circulation tank. The parallel structure doubles the circulation volume of the carbonization liquid, increases the contact area with CO2, promotes the carbonization synthesis rate, improves the CO2 utilization rate, shortens the carbonization reaction time, and obtains nano-calcium carbonate with narrow and regular particle size distribution.

[0051] The dispersant of this embodiment is a mixture of triethylhexyl phosphoric acid and sodium oleate in a mass ratio of 1:1.

[0052] (2) heating the carbonized liquid to 60° C., adding a saponified modifier I having a CaCO3 content of 2.5%, and stirring the mixture for 1 h to obtain a nano-calcium carbonate slurry. The nano-calcium carbonate slurry was pumped into a fully automatic plate-frame filter press at a pressure of 0.7 MPa, and the mixture was fed for 1 h and pressed for 1 h until the filter cake had a moisture content of 34.5%. The mixture was then sent to a dryer, and dried with blades in the first stage to obtain a moisture content of ≤5%, and then flash dried in the second stage to obtain a moisture content of ≤0.3%, thereby obtaining a nano-calcium carbonate powder.

[0053] The modifier I of this embodiment is prepared by mixing a long-chain fatty acid (50% stearic acid, 30% oleic acid, 20% arachidonic acid) and a chelated titanate coupling agent YB-401 (ethylene chelated pyrophosphate acyloxy titanate) in a mass ratio of 4:1; the method of use is as follows: 0.07 times the total mass of the long-chain fatty acid NaOH is placed in 18°C ​​water, heated to 85°C, stearic acid, oleic acid, and arachidonic acid are added and stirred for 30 minutes, and then the measured chelated titanate coupling agent is added, stirred evenly, and added to the calcium carbonate slurry to be added.

[0054] (3) conveying the nano-calcium carbonate powder into a continuous powder mixer, adding 1.5% of the mass of the nano-calcium carbonate powder as modifier II dropwise, stirring for 30 minutes, discharging and packaging, and obtaining the dealcoholized nano-calcium carbonate for silicone adhesive;

[0055] The modifier II of this embodiment is prepared by mixing isopropyl tri(dioctyl pyrophosphate) titanate and alkenyl triethoxysilane in a mass ratio of 1:1; the method of use is to dilute and mix the white oil and the modifier II in a mass ratio of 1:1, add them dropwise into a continuous mixing bin with a peristaltic pump, stir, and then discharge and package. The mixing bin has an orbital speed of 10r / min and an autorotational speed of 50r / min.

[0056] Example 2

[0057] A method for preparing nano calcium carbonate for dealcoholized silicone adhesive

[0058] (1) limestone is used as a raw material, and Ca(OH)2 refined slurry is obtained through calcination, digestion, screening and aging, and the Ca(OH)2 refined slurry is carbonized to obtain a carbonized liquid;

[0059] The limestone has a CaCO3 content of ≥98.5%, MgO ≤0.5%, a block diameter of 5-10 cm, a coke C of ≥78%, and a rock-coke ratio of 11.5:1;

[0060] The limestone is calcined at a temperature of 900° C. to 1000° C. for 85 hours to obtain overburned CaO having an oxalic acid detection activity of 8′;

[0061] Digest the overburned CaO with 90°C hot water, with an ash-water ratio of 1:8, and use a continuous rotary digester to digest until the Ca(OH)2 mass concentration reaches 12.5%, pass through a 100-mesh sieve, keep warm at 60°C for 110 hours, pass through a 325-mesh sieve, and add water to make the Ca(OH)2 refined slurry mass concentration reach 7%;

[0062] The Ca(OH)2 refined slurry is pumped into the high gravity reactor, the carbonization temperature is 19°C, the feed volume is 10m 3 , CO2 content 38%, flow rate 250L / min, reaction time 24min, endpoint pH control 6.5, add 0.7% dispersant, continue cyclic carbonization for 1min, stop carbonization, detect nano calcium carbonate pore size of 32nm, leave for 10h, and obtain carbonized liquid;

[0063] The high gravity reaction unit of this embodiment is the same as that of embodiment 1.

[0064] The dispersant in this embodiment is polyacrylamide.

[0065] (2) heating the carbonized liquid to 65° C., adding a saponified modifier I having a CaCO3 content of 2.8%, and stirring the mixture for 2 h to obtain a nano-calcium carbonate slurry, pumping the nano-calcium carbonate slurry into a fully automatic plate-frame filter press at a pressure of 0.7 MPa, feeding for 1 h, pressing for 1 h, pressing until the filter cake has a moisture content of 37%, and sending the mixture into a dryer, performing first-stage blade drying to obtain a moisture content of ≤5%, and second-stage flash drying to obtain a moisture content of ≤0.3%, to obtain a nano-calcium carbonate powder;

[0066] The modifier I of this embodiment is prepared by mixing a long-chain fatty acid (50% linear sodium alkyl sulfonate, 50% sodium α-olefin sulfonate) and a chelate titanate coupling agent QX-311W (a chelate solution of bis(dioctyl pyrophosphate) ethylene titanate and triethanolamine) in a mass ratio of 3:1; the method of use is to directly add the linear sodium alkyl sulfonate and the sodium α-olefin sulfonate into 25°C water, heat to 90°C, keep warm and stir for 60 minutes until completely dissolved, then add the measured chelate titanate coupling agent, stir well, and add to the calcium carbonate slurry.

[0067] (3) conveying the nano-calcium carbonate powder into a continuous powder mixer, adding 1.0% of the mass of the nano-calcium carbonate powder as modifier II dropwise, stirring for 40 minutes, discharging and packaging, and obtaining the dealcoholized nano-calcium carbonate for silicone adhesive;

[0068] The modifier II of this embodiment is prepared by mixing vegetable acid type monoalkoxy titanate (titanate coupling agent TC-F) and vinyl trimethoxy silane in a mass ratio of 2:1; the method of use is to dilute and mix isopropanol and the selected modifier II in a mass ratio of 1:1, and drip them into the continuous mixing bin by a peristaltic pump, stir for 30 minutes, and then discharge and package. The mixing bin has an orbital speed of 20r / min and an autorotational speed of 60r / min.

[0069] Example 3

[0070] A method for preparing nano calcium carbonate for dealcoholized silicone adhesive

[0071] (1) limestone is used as a raw material, and Ca(OH)2 refined slurry is obtained through calcination, digestion, screening and aging, and the Ca(OH)2 refined slurry is carbonized to obtain a carbonized liquid;

[0072] The limestone has a CaCO3 content of ≥98.5%, MgO ≤0.5%, a block diameter of 5-10 cm, a coke C of ≥78%, and a rock-coke ratio of 10:1;

[0073] The limestone is calcined at a temperature of 950° C. to 1000° C. for 60 hours to obtain overburned CaO having an oxalic acid detection activity of 8′;

[0074] Digest the overburned CaO with 90°C hot water, with an ash-water ratio of 1:7, and use a continuous rotary digester to digest until the Ca(OH)2 mass concentration reaches 10%, pass through a 100-mesh sieve, keep warm at 70°C for 130 hours, pass through a 325-mesh sieve, and add water to make the Ca(OH)2 refined slurry mass concentration reach 6%;

[0075] The Ca(OH)2 refined slurry is pumped into the high gravity reactor, the carbonization temperature is 21℃, and the feed volume is 8m 3, CO2 content 45%, flow rate 180L / min, reaction time 18min, endpoint pH control 6.7, add dispersant 0.85%, continue cyclic carbonization for 1min, stop carbonization, detect nano calcium carbonate pore size of 28nm, leave for 5h, and obtain carbonized liquid;

[0076] The high gravity reaction unit of this embodiment is 3 high gravity reactors connected in parallel to the same carbonized liquid circulation tank;

[0077] The dispersant in this embodiment is sodium lauryl sulfate.

[0078] (2) heating the carbonized liquid to 70° C., adding a saponified modifier I having a CaCO3 content of 3.0%, and stirring the mixture for 2 h to obtain a nano-calcium carbonate slurry. The nano-calcium carbonate slurry was pumped into a fully automatic plate-frame filter press at a pressure of 0.7 MPa, and the feed was fed for 1 h and pressed for 1 h until the filter cake had a moisture content of 36%. The mixture was then sent to a dryer, and dried with blades in the first stage to obtain a moisture content of ≤5%, and then flash dried in the second stage to obtain a moisture content of ≤0.3%, thereby obtaining a nano-calcium carbonate powder.

[0079] The modifier I of this embodiment is prepared by mixing a long-chain fatty acid (40% monoalkyl phosphate, 40% dialkyl phosphate, and 20% trialkyl phosphate) and a chelated titanate coupling agent KR-138S (bis(dioctyl pyrophosphate) glycolate titanate) in a mass ratio of 4:1; the method of use is to directly add the monoalkyl phosphate, dialkyl phosphate, and trialkyl phosphate into 10°C water, heat to 90°C, keep warm and stir for 60 minutes until completely dissolved, then add the measured chelated titanate coupling agent, stir well, and add to the calcium carbonate slurry to be added.

[0080] (3) conveying the nano-calcium carbonate powder into a continuous powder mixer, adding 0.8% of the mass of the modifier II to the nano-calcium carbonate powder, stirring for 50 minutes, discharging and packaging, and obtaining the dealcoholized nano-calcium carbonate for silicone adhesive;

[0081] The modifier II of this embodiment is prepared by mixing composite phosphoric acid type monoalkoxy titanate and vinyl trimethoxy silane in a mass ratio of 1:1; the method of use is to dilute and mix ethanol and the selected coupling agent in a 1:1 ratio, add them dropwise into a continuous mixing bin by a peristaltic pump, stir for 30 minutes, and then discharge and package. The mixing bin has an orbital speed of 10 r / min and an autorotational speed of 60 r / min.

[0082] Example 4

[0083] A method for preparing nano calcium carbonate for dealcoholized silicone adhesive

[0084] (1) limestone is used as a raw material, and Ca(OH)2 refined slurry is obtained through calcination, digestion, screening and aging, and the Ca(OH)2 refined slurry is carbonized to obtain a carbonized liquid;

[0085] The limestone has a CaCO3 content of ≥98.5%, MgO ≤0.5%, a block diameter of 5-10 cm, a coke C of ≥78%, and a rock-coke ratio of 11:1;

[0086] The limestone is calcined at a temperature of 1000° C. to 1100° C. for 50 hours to obtain overburned CaO having an oxalic acid detection activity of 10′;

[0087] Digest the overburned CaO with 98°C hot water, with an ash-water ratio of 1:6, and use a continuous rotary digester to digest until the Ca(OH)2 mass concentration reaches 9%, pass through a 100-mesh sieve, keep warm at 70°C for 150 hours, pass through a 325-mesh sieve, and add water to make the Ca(OH)2 refined slurry mass concentration reach 5.5%;

[0088] The Ca(OH)2 refined slurry is pumped into the high gravity reactor, the carbonization temperature is 22℃, the feed volume is 5m 3 , CO2 content 40%, flow rate 105L / min, reaction time 16min, endpoint pH control 6.7, add dispersant 1.0%, continue cyclic carbonization for 1min, stop carbonization, detect nano calcium carbonate pore size of 25nm, leave for 6h, and obtain carbonized liquid;

[0089] The high gravity reaction unit of this embodiment is the same as that of embodiment 3.

[0090] The dispersant of this embodiment is a mixture of polyacrylamide and sodium oleate in a mass ratio of 2:1.

[0091] (2) heating the carbonized liquid to 75° C., adding a saponified modifier I having a CaCO3 content of 3.5%, and stirring the mixture for 3 h to obtain a nano-calcium carbonate slurry, pumping the nano-calcium carbonate slurry into a fully automatic plate-frame filter press at a pressure of 0.7 MPa, feeding for 0.5 h, pressing for 1 h, pressing until the filter cake has a moisture content of 35.5%, and sending the mixture into a dryer, performing a first-stage blade drying to obtain a moisture content of ≤5%, and a second-stage flash drying to obtain a moisture content of ≤0.3%, to obtain a nano-calcium carbonate powder;

[0092] The modifier I of this embodiment is prepared by mixing a long-chain fatty acid (50% stearic acid, 30% linolenic acid, 20% eicosylene acid) and a chelated titanate coupling agent QX-311W (a chelate solution of bis(dioctyloxypyrophosphate)ethylene titanate and triethanolamine) in a mass ratio of 2:1; the method of use is to place 0.07 times the total mass of the long-chain fatty acid in 10°C water, heat to 85°C, add the long-chain fatty acid and stir for 20 minutes, then add the measured chelated titanate coupling agent, stir well, and add to the calcium carbonate slurry to be added.

[0093] (3) conveying the nano-calcium carbonate powder into a continuous powder mixer, adding 1.0% of the mass of the nano-calcium carbonate powder as modifier II dropwise, stirring for 30 minutes, discharging and packaging, and obtaining the dealcoholized nano-calcium carbonate for silicone adhesive;

[0094] The modifier II of this embodiment is prepared by mixing tetraisopropyl di(dioctylphosphite) titanate and vinyl tri(β-methoxyethoxy) silane coupling agent in a mass ratio of 1:1; the method of use is to dilute and mix ethanol and the selected coupling agent in a 1:1 ratio, add them dropwise into a continuous mixing bin by a peristaltic pump, stir for 30 minutes, and then discharge and package them; the mixing bin has an orbital speed of 20 r / min and an autorotational speed of 60 r / min.

[0095] Comparative Example 1

[0096] Preparation method of nano calcium carbonate

[0097] (1) limestone is used as a raw material, and Ca(OH)2 refined slurry is obtained through calcination, digestion, screening and aging, and the Ca(OH)2 refined slurry is carbonized to obtain a carbonized liquid;

[0098] The limestone has a CaCO3 content of ≥98.5%, MgO ≤0.5%, a block diameter of 5-10 cm, a coke C of ≥78%, and a rock-coke ratio of 10:1;

[0099] The limestone is calcined at a temperature of 800° C. to 900° C. for 60 hours to obtain overburned CaO having an oxalic acid detection activity of 3′;

[0100] Digest the overburned CaO with 70°C hot water, with an ash-water ratio of 1:8, and use a continuous rotary digester to digest until the Ca(OH)2 mass concentration reaches 14.5%, pass through a 100-mesh sieve, and age at 38°C for 60 hours, pass through a 325-mesh sieve, and add water to make the Ca(OH)2 refined slurry mass concentration reach 7%;

[0101] The Ca(OH)2 refined slurry was pumped into the high gravity reactor, the carbonization temperature was 19°C, and the feed volume was 5m 3 , CO2 content 38%, flow rate 150L / min, reaction time 38min, endpoint pH control 6.5, stop carbonization, leave for 5h, and obtain carbonized liquid; the ultragravity reactor of this comparative example is the same as that of Example 1;

[0102] (2) heating the carbonized liquid to 65° C., adding saponified stearic acid with a CaCO3 content of 4.4%, and stirring for 2 h to obtain a nano-calcium carbonate slurry, pumping the nano-calcium carbonate slurry into a fully automatic plate-frame filter press at a pressure of 0.7 MPa, feeding for 1 h, pressing for 1 h, pressing until the filter cake has a moisture content of 37%, and sending it to a dryer, performing a first-stage blade drying with a moisture content of ≤5%, and a second-stage flash drying with a moisture content of ≤0.35%, to obtain a nano-calcium carbonate powder;

[0103] (3) conveying the nano calcium carbonate powder into a continuous powder mixer, discharging and packaging the powder, and obtaining a nano calcium carbonate finished product;

[0104] The nano calcium carbonate prepared in the embodiment and the comparative example was subjected to performance testing, and the testing method was as follows:

[0105] Moisture content: Determined in accordance with 3.13 of GB / T 19281-2014.

[0106] pH value: Determined in accordance with 3.18 of GB / T 19281-2014.

[0107] BET: Weigh 0.05g-0.50g, accurate to 0.0001g, and measure according to the method specified in GB / T 19587.

[0108] Extrusion volume: 12,000 107:CaCO3=1:1, stirred in a high-speed mixer for 15 minutes, extrusion volume in 1 minute at an extruder pressure of 0.4MPa and a hole of 3mm.

[0109] Pore ​​size: Weigh 1 g of sample and measure it on F-Sorb3400 specific surface area and pore size analyzer.

[0110] D 50 , D 100 : Weigh 0.02g of CaCO3 sample, dissolve it in non-ionic surfactant, add 40ml of distilled water, perform external ultrasound for 10min, and detect it with a laser particle size analyzer.

[0111] The test results are shown in Table 1.

[0112] Table 1 Nano calcium carbonate performance test results

[0113]

[0114]

[0115] As can be seen from Table 1, the nano calcium carbonate of the present invention has a moderate specific surface area, low moisture and pH value, can effectively reduce the modulus of the adhesive, and the high extrusion volume can improve the elongation of the adhesive. The pore size is uniform and the laser particle size is small, indicating that the product has uniform particle size and good dispersion.

[0116] Example 5

[0117] A single-component dealcoholized adhesive is prepared using the nano-calcium carbonate of Examples 1-4 and Comparative Example 1 as raw materials, and the finished products are recorded as Samples 1-4 and Comparative Samples. The single-component dealcoholized adhesive is made of the following components calculated by weight:

[0118] 107 glue, 360 parts, viscosity 12000mPa.s;

[0119] Silicone oil, 36 parts, viscosity 350mPa.s;

[0120] 360 parts of nano calcium carbonate, prepared by the methods of Examples 1-4 and Comparative Example 1;

[0121] Silane coupling agent KH550, 18 parts;

[0122] Silane coupling agent KH560, 20 parts;

[0123] Methyldimethylsilane, 15 parts;

[0124] Organic titanium Tyzor catalyst ( 726), 8 copies.

[0125] The preparation method of the single-component dealcoholized glue is:

[0126] First, put 107 glue, silicone oil and calcium carbonate into the kettle, stir manually to remove powder, and place it on a planetary mixer; start stirring at a speed of 15Hz for 15min; stop, rub the edge, start stirring at a speed of 40Hz, vacuum -0.08MPa or above, and time for 2h; stop, add silane coupling agent KH550, silane coupling agent KH560, methyltrimethylsilane and catalyst, start stirring at a speed of 35Hz, vacuum -0.08MPa or above, and time for 20min; stop, empty, pour glue, and measure extrusion and surface drying time; prepare glue strips on the template, with the requirements of: smooth, particle-free, and pore-free, place at standard temperature and humidity for 7d, and perform tensile strength and elongation at break performance tests and modulus calculations; prepare I-shaped parts, place them under standard conditions for 21d to test bonding strength; the test method is:

[0127] Surface drying time and surface drying time after 6 months storage: Tested according to the method specified in GB / T 13477.5.

[0128] Tensile strength and elongation at break: Tested according to the method specified in GB / T 528, using a 2.0±0.2mm thick type 1 dumbbell specimen.

[0129] Modulus: tensile strength N divided by the cross-sectional area A of the rubber strip.

[0130] Adhesion strength: Tested according to the method specified in 6.8 of GB / T 16776-2005.

[0131] Extrusion and extrusion after 6 months of storage: Test according to the method specified in 6.4 of GB / T 16776.

[0132] The test results are shown in Table 2.

[0133] Table 2 Single component dealcoholization adhesive performance test results

[0134]

[0135] It can be seen from Table 2 that the nano calcium carbonate prepared by the embodiment of the present invention can meet the use requirements of the single-component dealcoholized silicone adhesive, with low modulus, high elongation, high adhesion, and maintaining the storage stability of the adhesive.

[0136] It should be noted that when the claims of the present invention involve numerical ranges, it should be understood that the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. In order to avoid redundancy, the present invention describes a preferred embodiment.

[0137] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0138] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A one-component dealcoholized silicone adhesive, characterized in that: Calculated by weight, it is made of the following components: 107 glue, 360 copies; Silicone oil, 36 parts; Nano calcium carbonate, 360 parts; Silane coupling agent KH550, 18 parts; Silane coupling agent KH560, 20 parts; Methyldimethylsilane, 15 parts; Organic titanium catalyst, 8 parts; The one-component dealcoholized nano-calcium carbonate for silicone adhesive is prepared by the following steps: S1, crushing, calcining, digesting, screening and aging limestone with high CaCO3 content to obtain Ca(OH)2 refined pulp; S2, carbonizing the Ca(OH)2 refined pulp to obtain a carbonized liquid; the carbonization is specifically: Pump the Ca(OH)2 refined slurry into the high gravity reactor at a temperature of 18°C-22°C and a feed volume of 5-10m 3 , CO2 content 35%-45%, flow rate 55-250L / min, reaction time 15-25min, endpoint pH control 6.5-6.8, add Ca(OH)2 seminal slurry mass 0.5%-1.0% dispersant, continue cyclic carbonization for 1min, stop carbonization, and place for 5-10h; the dispersant is sodium dodecyl sulfate; S3, heating the carbonized liquid to 55-75°C, adding a modifier I having a calcium carbonate content of 2.5%-3.5%, and stirring at this temperature for 1h-3h to obtain a nano-calcium carbonate slurry, and obtaining a nano-calcium carbonate powder after filter pressing and drying; S4, adding 0.5%-1.5% of the mass of modifier II to the nano-calcium carbonate powder based on the dry calcium carbonate, stirring for 0.5-1h to obtain the single-component dealcoholized nano-calcium carbonate for silicone adhesive; The modifier I is prepared by mixing a high-grade phosphate and a chelate titanate coupling agent in a mass ratio of 4:1, wherein the high-grade phosphate is compounded by 40% monoalkyl phosphate, 40% dialkyl phosphate and 20% trialkyl phosphate, and the chelate titanate coupling agent is bis(dioctyl pyrophosphate)hydroxyacetate titanate; The modifier II is prepared by mixing composite phosphoric acid type monoalkoxy titanate and vinyl trimethoxy silane in a mass ratio of 1:

1.

2. The one-component dealcoholized silicone adhesive according to claim 1, characterized in that: The limestone has a CaCO3 content of ≥98.5%, MgO ≤0.5%, a block diameter of 5-10 cm, a coke C of ≥78%, a rock-coke ratio of 10-12:1, a calcination temperature of 800°C-1100°C, a calcination time of 48h-96h, and calcination to obtain overburned CaO with an oxalic acid detection activity of 5'-10'.

3. The one-component dealcoholized silicone adhesive according to claim 2, characterized in that: The digestion, screening and aging are specifically as follows: add 80-100°C hot water to digest the overburned CaO, with an ash-to-water ratio of 1:5-8, and use a continuous rotary digester to digest until the Ca(OH)2 mass concentration is 9%-15%, pass through a 100-mesh sieve, keep warm at 50°C-70°C for aging for 100-150h, pass through a 325-mesh sieve, and add water to adjust the Ca(OH)2 refined slurry mass concentration to 5%-8%.

4. The one-component dealcoholized silicone adhesive according to claim 3, characterized in that: The supergravity reaction unit is composed of 2-3 supergravity reactors connected in parallel on the same carbonized liquid circulation tank.

Citation Information

Patent Citations

  • Production method of special nano calcium carbonate for dual-component high-extrudability building silicone adhesive

    CN104804473A

  • High-displacement flame-retardant silicone sealant and preparation method thereof

    CN115595114A